2023
DOI: 10.1371/journal.pone.0283633
|View full text |Cite
|
Sign up to set email alerts
|

VA’s implementation of universal screening and evaluation for the suicide risk identification program in November 2020 –Implications for Veterans with prior mental health needs

Abstract: Importance United States Veterans are at higher risk for suicide than non-Veterans. Veterans in rural areas are at higher risk than their urban counterparts. The coronavirus pandemic intensified risk factors for suicide, especially in rural areas. Objective To examine associations between Veterans Health Administration’s (VA’s) universal suicide risk screening, implemented November 2020, and likelihood of Veterans being screened, and receiving follow-up evaluations, as well as post-screening suicidal behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Apart from laws and policies, universal screening for suicide is another effective public health prevention approach. Universal screening will aid the detection of at-risk individuals for whom targeted interventions can be implemented, and it helps to reduce disparities and bias by ensuring that all individuals are screened across all demographic groups, communities, and care settings [ 37 - 39 ]. Such target interventions include conversations with such individuals and their families and loved ones as appropriate to restrict access to firearms, including safety locks [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from laws and policies, universal screening for suicide is another effective public health prevention approach. Universal screening will aid the detection of at-risk individuals for whom targeted interventions can be implemented, and it helps to reduce disparities and bias by ensuring that all individuals are screened across all demographic groups, communities, and care settings [ 37 - 39 ]. Such target interventions include conversations with such individuals and their families and loved ones as appropriate to restrict access to firearms, including safety locks [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Past work has supported the validity of the PHQ-9 (e.g., Kroenke et al, 2001) and the use of a single-item measure of suicidal ideation (Desseilles et al, 2012). Notably, this item has been used as a screen for suicidality in the VA's suicide risk identification program (Gujral et al, 2023) and in previous work assessing suicidal ideation among veterans (e.g., Elbogen et al, 2020;Hoffmire et al, 2022).…”
Section: Suicidal Ideationmentioning
confidence: 95%
“…McGuire et al (2023) found that veterans' social isolation since COVID-19 became significant and resulted in worse mental health outcomes [18]. Gujral et al (2023) pursued the impact of COVID-19 on veterans' suicide risk within the healthcare system [19]. Akhtar et al (2023) summarized that COVID-19 increased the risk of cardiovascular illness [20].…”
Section: Covid-19 Impacts On Healthmentioning
confidence: 99%